Recent increase in species-wide diversity after interspecies introgression in the highly endangered Iberian lynx - Lucena-Perez, Maria; Paijmans, Johanna; Nocete, Francisco; Nadal, Jordi; Detry, Cleia; Dalén, Love; Hofreiter, Michael; Barlow, Axel; Godoy, José (Nature Ecology & Evolution, 2024)
Genetic diversity is lost in small and isolated populations, affecting many globally declining species. Interspecific admixture events can increase genetic variation in the recipient species’ gene pool, but empirical examples of species-wide restoration of genetic diversity by admixture are lacking. Here we present multi-fold coverage genomic data from three ancient Iberian lynx (Lynx pardinus) approximately 2,000–4,000 years old and show a continuous or recurrent process of interspecies admixture with the Eurasian lynx (Lynx lynx) that increased modern Iberian lynx genetic diversity above that occurring millennia ago despite its recent demographic decline. Our results add to the accumulating evidence for natural admixture and introgression among closely related species and show that this can result in an increase of species-wide genetic diversity in highly genetically eroded species. The strict avoidance of interspecific sources in current genetic restoration measures needs to be carefully reconsidered, particularly in cases where no conspecific source population exists.